PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS HIGHER ORDER THINKING SKILLS (HOTS) PADA MATA PELAJARAN MATEMATIKA KELAS IV SDN 01 KEMIRI - Nunik Miftakul Jannah; Mira Azizah; Sunan Baedowi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The background that prompted this researcher was the teacher student worksheets in teaching in class which found that teachers still use Low Order Thinking Skill (LOTS) based student worksheets which contain multiple choice questions and short entries that do not integrate questions in the form of skills. higher order thinking into student worksheets. This study aims to determine the validity and practicality of Student Worksheets (LKPD) based on Higher Order Thinking Skills (HOTS) in Mathematics class IV at SDN 01 Kemiri. This type of research is Research and Development proposed by Sugiyono by using the development procedure up to stage seven, namely revising the product. The results showed that Student Worksheets (LKPD) based on Higher Order Thinking Skills (HOTS) were valid and practical for grade IV elementary school students with intervals of 81% -100% included in the "Very Eligible" category.